1998
DOI: 10.1086/516278
|View full text |Cite
|
Sign up to set email alerts
|

First Outbreak of Human Trichinellosis Caused by Trichinella pseudospiralis

Abstract: This is the first report of an epidemic of human infection with Trichinella pseudospiralis. An outbreak of trichinellosis affecting 59 individuals, of whom one died, occurred in southern Thailand during 1994 -1995. The source of this epidemic was raw pork from a wild pig that was distributed to villagers by a local hunter. The most striking clinical features among 50 individuals who could be followed were muscular swelling, myalgia, and asthenia persisting for ú4 months. These were associated with significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(42 citation statements)
references
References 14 publications
0
42
0
Order By: Relevance
“…Jongwutiwes et al (1998) reported elevated levels of CPK, LDH, AST and ALT in human patients infected with Trichinella pseudospiralis. Increased serum levels of ALT in pigs infected with T. spiralis have also been previously reported (Ribicich et al 2007).…”
Section: Introductionmentioning
confidence: 94%
“…Jongwutiwes et al (1998) reported elevated levels of CPK, LDH, AST and ALT in human patients infected with Trichinella pseudospiralis. Increased serum levels of ALT in pigs infected with T. spiralis have also been previously reported (Ribicich et al 2007).…”
Section: Introductionmentioning
confidence: 94%
“…In addition to these marked characteristics, T. pseudospiralis is also dissimilar to other species by a smaller length in larvae and adults (Table 1), moderate reproductive capacity in rats, and, with T. britovi, moderate reproductive capacity in pigs (Kapel and Gamble, 2000) and in wild boars (Kapel, 2000). In recent years, human outbreaks from swine have been reported (Jongwutiwes et al, 1998;Britov, 1997).…”
Section: T Murrellimentioning
confidence: 99%
“…Indeed, human cases of the disease have been documented in 55 (27.8%) countries around the world (Pozio 2007). By far, the major causative agent of trichinellosis is T. spiralis (Vorou et al 2007) although cases of human infection caused by other Trichinella species, including Trichinella pseudospiralis, Trichinella nativa, Trichinella murrelli and Trichinella britovi have been reported ( Jongwutiwes et al 1998;Pozio 2001). The major reservoir host for T. spiralis is the domestic pig which has been responsible for a growing number of outbreaks of trichinellosis in eastern European countries since the break-up of the USSR in the early 1990s (Pozio 2001).…”
Section: Zoonotic Nematode Infections (A) Trichinellosismentioning
confidence: 99%